Analysis of output voltage ripple for dual randomized PWM buck converter operating in continuous and discontinuous conduction modes - Boudouda, Aimad; Boudjerda, Nasserdine; Nafa, Fares (Acta Polytechnica, 2022)
Dual Randomized Pulse Width Modulation (DRPWM) is renowned for its better effectiveness than Simple Randomized Pulse Width Modulation (SRPWM) in reducing conducted Electro-Magnetic Interferences (EMI) in power converters. However, the introduction of low-frequency ripples into the output voltage by dual randomization has not yet been addressed; this effect is investigated in this paper for a buck converter operating in both the continuous conduction mode (CCM) and the discontinuous conduction mode (DCM). First, the modulating principle is presented. Then, a general analytical expression for power spectral density (PSD) of the input current is derived and validated for the proposed DRPWM scheme for both the CCM and DCM. A comparison of the PSDs of the input current for all RPWM schemes in both the CCM and DCM shows the PSD spreading effectiveness of the dual scheme as compared to simple schemes. Finally, the low-frequency output ripple is analysed using the PSD of output voltage. The results reveal that the output voltage ripple is affected by all the randomized schemes in both the CCM and the DCM. Also, the dual scheme (RCFM-RPPM) introduces the highest low-frequency voltage ripple, especially in the CCM and for low duty cycles. In DCM, the RPPM scheme gives the lowest voltage ripple, while the RCFM scheme gives the lowest voltage ripple in the CCM. The results are confirmed by both theory and simulations.